Development of Computer-Based Learning Tools and Media at Sekolah Menengah Pertama (SMP) Muhammadiyah Tanjung - Tri Wahyono; Berli P. Kamiel; Fitroh Anugerah K Yudha; M. Budi Nur Rahman; Krisdiyanto Krisdiyanto (OJS Universitas Muhammadiyah Gresik, 2023)
Knowledge and skills about computer and information technology should be taught to students from an early age. These skills are needed when continuing education to the next level. Junior high school students really need these skills to equip them to face technological developments and advances towards more sophisticated developments. To be able to achieve this goal, adequate infrastructure is needed so that the learning process of computer and information technology can run smoothly and effectively. Until now, learning about computer and information technology at SMP Muhammadiyah Tanjung has not been implemented due to the unavailability of computer equipment that can be used by students. Through this PPM Muhammadiyah scheme community service program, a computer room and laboratory will be gradually developed at SMP Muhammadiyah Tanjung according to the available budget so that it can be used as a learning room and practice of computer and information technology for students. The method used is in collaboration with Mechanical Engineering Study Program and SMP Muhammadiyah Tanjung, Kec. Muntilan, Kab. Magelang for the design and supply of sufficient tools. With this Muhammadiyah PPM scheme service program, it is hoped that students will be able to skillfully operate computer units and can develop skills and use information technology in a better direction.